Effect of Bimetal Oxide ZnO/ZnS Nanocomposite Doped TiO2 on the Performance of Dye-Sensitized Solar Cell - Jameel Owaid, Hind; Baqer Alwan, Taghreed; Muwafaq Abdalhadi, Saifaldeen (Al-Nahrain Journal of Science, 2025)
Dye-sensitized solar cells (DSSC) have garnered significant interest in recent years because of their comparatively affordable production expenses and the potential to utilize flexible and transparent substrates. A widely used approach to enhance the efficiency of DSSCs is the optimization of the photoanode components by the introduction of metal or metal oxide doping in TiO2 nanostructures. In this work, the exclusive gel technique is used to produce nanoparticles of TiO2, ZnO, and ZnS. Additionally, we prepared a ZnO/ZnS nanocomposite by mixing these materials in specific weights in an ethanolic solution. All prepared materials were characterized using scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), and high-resolution X-ray diffraction (XRD). The doctor blade approach was used to prepare three kinds of photoanode in DSSC. These photoanodes were made by adding a co-dopant, ZnO/ZnS, in different weights (2%, 4%, and 6%) into TiO2 nanoparticles. The 6% wt of ZnO/ZnS doped TiO2 resulted in an enhancement in power conversion efficiency (PCE), reaching 4.92 %. This may be attributed to an increase in the short-circuit current density (Jsc) to 9.60 mA/cm2 and the open-circuit voltage (Voc) to 0.81 V, which represents a 20% enhancement compared to the undoped photoanode.